Time Trend of the People lost follow up on Antiretroviral Therapy (ART) Services in Nepal: A Epidemiological Modelling - Sathian, Brijesh; Adhikari, Sudhir; Sreedharan, Jayadevan; Banerjee, Indrajit; Roy, Bedanta; Elayedath, Rajesh (Indian Journal of Community Health, 2014)
Background: The real state about the spread of the HIV epidemic in Nepal is not clear since the details available are on the basis of repeated integrated biological and behavioral surveillance. Objective To study the trends of People lost follow up on ART in future. Material and methods: A retrospective study was carried out on the data collected from the Health ministry records of Nepal, between 2006 and 2012. Descriptive statistics and statistical modelling were used for the analysis and forecasting of data. Results: Including the constant term from the equation, the quadratic model was the best fit, for the forecasting of People lost follow up on ART. Using quadratic equation, it is estimated that 4331 reported number of People lost follow up on ART will be there in Nepal by the year 2020. Conclusion: The People lost follow up on ART in Nepal are having an increasing trend. Estimates of the total number of People lost follow up on ART attributable to the major routes of infection make an important contribution to public health policy. They can be used for the planning of healthcare services and for contributing to estimates of the future numbers with People lost follow up on ART used for planning health promotion programmes.